2017
DOI: 10.1002/ejoc.201701584
|View full text |Cite|
|
Sign up to set email alerts
|

Design and Synthesis of Building Blocks for PPII‐Helix Secondary‐Structure Mimetics: A Stereoselective Entry to 4‐Substituted 5‐Vinylprolines

Abstract: In the course of our studies towards the synthesis of proline-based secondary-structure mimetics, we developed a straightforward methodology for the diastereoselective preparation of 4-alkyl-5-vinyl-substituted proline derivatives. Starting from N-Boc-protected tert-butyl pyroglutamate, α-alkylation, lactam reduction and acid-catalyzed methanolysis afforded 4-alkyl-5-methoxyproline derivatives. After BF 3 -induced formation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 49 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…The compounds employed in this study were synthesized by modular assembly of the building blocks using established coupling protocols ( 40 ). The required ProM scaffolds ProM-1 ( 41 , 43 ), ProM-2 ( 45 ), ProM-9 ( 46 ), ProM-13 ( 46 ), ProM-15 ( 47 ), and ProM-17 ( 47 ) ( Fig. 1 B ) were synthesized as separately published.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The compounds employed in this study were synthesized by modular assembly of the building blocks using established coupling protocols ( 40 ). The required ProM scaffolds ProM-1 ( 41 , 43 ), ProM-2 ( 45 ), ProM-9 ( 46 ), ProM-13 ( 46 ), ProM-15 ( 47 ), and ProM-17 ( 47 ) ( Fig. 1 B ) were synthesized as separately published.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason the alkylated derivatives of ProM-1, i.e., ProM-9 and ProM-13 ( Fig. 1 B ), were synthesized ( 46 ) and used to prepare the desired inhibitors 6 and 7 ( Table 1 ). Affinity measurements then showed that both inhibitors outperformed 1 substantially and lowered the to 380 nM ( 6 ) and 120 nM ( 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of the method was demonstrated in the stereo-divergents ynthesis of ProM-15 and related cyclic, proline-derived dipeptide mimetics, which represent attractive building blocks for the development of modularp eptide-inspired bioactive molecules with ad efined three-dimensional structure.C urrent investigationsi no ur laboratory are focused on the further exploration of the developed N-allylation protocol with respect to mechanistic aspects, the evaluation of the substrates cope and applications in natural-product synthesis. Moreover, we are currently expanding our ProMt oolbox [1][2][3]19] with further ProM-15-related compounds, which are then incorporated as modulesi nto PPII-helix secondary structure mimetics acting as inhibitors of disease-relevant protein-interactions.…”
mentioning
confidence: 99%
“…In the original article, we inadvertently swapped structures 8 and 9 at the top of Table (on page 457). We apologize for this error.…”
Section: Diastereoselective Vinylation Of 5‐methoxy‐prolines Of Typementioning
confidence: 99%